PENGARUH PIUTANG DAN UKURAN PERUSAHAAN TERHADAP SALES GROWTH - Adi Irawan Setiyanto; Nurzilla Nurzilla (Politeknik Negeri Batam, 2019)
This study aims to obtain empirical evidence of several factors that affect the company's sales growth, namely the influence of Accounts Receivable, Firm Age and Firm Size to Sales Growth of companies in the manufacturing sector of consumer goods listed on the Indonesia Stock Exchange (IDX) period 2012-2016. The dependent variable of sales growth is measured by the proxy of the company's sales amount. Independent Variables Receivables are measured by the firm's receivable account value, the firm's age variable is measured by age since the company stands and the firm size variable is measured by the total assets owned by the company. This research method using approach of quantitative method. The sample was chosen using purposive sampling method with certain criteria and obtained as many as 140 samples of manufacturing companies that meet the criteria. Data analysis technique used is panel data regression analysis. The results of this study indicate that accounts receivable & firm size affect the company's sales growth. While the age of the company does not affect the company's sales growth.